Penerapan Model Pembelajaran Cooperative Learning Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Kelas V MI Cokroaminoto Bandingan Banjarnegara - Ratih Ida Tristanti; Sri Jumini (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This study was conducted to determine: (1) How are teacher activities in learning Indonesian using the Cooperative Learning learning model to improve student learning outcomes in class V MI Cokroaminoto Bandingan Banjarnegara. (2) How is student activity in learning Indonesian using the Cooperative Learning learning model to improve student learning outcomes in class V MI Cokroaminoto Bandingan Banjarnegara. (3) Is the application of the Cooperative Learning learning model able to improve student learning outcomes in class V MI Cokroaminoto Bandingan Banjarnegara. This type of research is Classroom Action Research which consists of two cycles. In each cycle, one meeting is held. Each cycle consists of four steps, namely planning, implementation, observation, reflection. The subjects in this study were students of class V MI Cokroaminoto Bandingan Banjarnegara with a total of 20 students, consisting of 6 boys and 14 girls. The results of observations of teacher activities in implementing Cooperative Learning during Indonesian Language learning in cycle I obtained a score of 84 with good criteria, while in cycle II it increased with a score of 86 and obtained very good criteria. Based on data analysis, the application of the Cooperative Learning learning model can improve student learning outcomes in Indonesian Language mutants of class V at MI Cokroaminoto Bandingan Banjarnegara. The percentage of student learning completion in cycle I was 55%, while the percentage in cycle II was 70%. There was an increase of 15% from the previous cycle and has achieved the predetermined success indicators. And the application of the Cooperative Learning learning model can increase student activity in Indonesian Language mutants of class V at MI Cokroaminoto Bandingan Banjarnegara. The percentage of student activity in class in cycle I, cycle II was 55.10% and 66.70%. This percentage shows an increase in student activity and has achieved the predetermined success indicators.